DETERMINATION OF OPTIMAL ANNEALING TEMPERATURE Vibrio alginolyticus PRIMERS USING POLYMERASE CHAIN REACTION METHOD - Putri, Gladys Indira; Nurjayadi, Muktiningsih; Declan, Jefferson Lynford; Krisdawati, Ismaya; Juliansyah, Dandy Akbar; Fahriza, Tiara; Azzahra, Maharanianska; Maulana, Irvan; Kartika, Irma Ratna; Kurniadewi, Fera; Sukmawati, Dalia; Saamia4, Vira; Saputro, Dwi Anna Oktaviani; Wiranatha, I Made; Abomoelak, Bassam; El-Enshasy, Hesham Ali (BRIN - Badan Riset dan Inovasi Nasional, 2023)
Food poisoning is a global issue of grave concern. If food is not properly cooked, it can be a medium for the spread of pathogenic bacteria. Vibrio alginolyticus is one of the pathogenic bacteria that can cause food poisoning. real-time Polymerase Chain Reaction (rt-PCR) can detect pathogenic bacteria in food, so it is necessary to determine the optimal annealing temperature. This research aims to obtain the optimal annealing temperature of the Va_Chr1_FR primer using Gradient PCR. The DNA concentration used was 174.5 with an A260/A280 purity of 1.94. The temperature range tested, 53°C-62°C, corresponds to the melting temperature of the Va_Chr1_FR primers. The primers designed were F5'-TTCTTCTGTTGTAGGTTCCG-F3' and R5'-CCAGCCCTCACATCTAATAC-R3'. Based on these results, a temperature of 60°C is deemed as the most optimal annealing temperature because it produces one of the brightest bands on electrophoresis with an amplicon length of 146 bp. The findings of this study will be beneficial to the development of Va_Chr1_FR Vibrio alginolyticus primers testing on food samples using the real-time PCR method.